2020
DOI: 10.1177/0267659120946733
|View full text |Cite
|
Sign up to set email alerts
|

Normoxic management of cardiopulmonary bypass reduces myocardial oxidative stress in adult patients undergoing coronary artery bypass graft surgery

Abstract: Introduction: We aimed to investigate whether normoxic cardiopulmonary bypass would limit myocardial oxidative stress in adults undergoing coronary artery bypass grafting. Methods: Patients scheduled to undergo elective isolated on-pump coronary artery bypass grafting were randomized to normoxia and hyperoxia groups. The normoxia group received 35% oxygen during anesthetic induction, 35% during hypothermic bypass, and 45% during rewarming. The hyperoxia group received 70%, 50%, and 70% oxygen, respectively. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Potential reasons hyperoxia may be harmful in patients having cardiac surgery utilizing CPB are cardiovascular dysfunction, 28,29 enhancement of ischemia-reperfusion injury, 30,31 and direct injury from reactive oxygen species. [32][33][34][35] However, we did not find evidence of such harm in our study, at least that manifested as cognitive dysfunction. In interpreting these results, it is entirely plausible that the arterial oxygen content is a minor variable in the response to ischemia-reperfusion injury, dwarfed by that from the systemic inflammatory response to CPB.…”
Section: Intraoperative Oxygen and Cognition After Surgerycontrasting
confidence: 89%
“…Potential reasons hyperoxia may be harmful in patients having cardiac surgery utilizing CPB are cardiovascular dysfunction, 28,29 enhancement of ischemia-reperfusion injury, 30,31 and direct injury from reactive oxygen species. [32][33][34][35] However, we did not find evidence of such harm in our study, at least that manifested as cognitive dysfunction. In interpreting these results, it is entirely plausible that the arterial oxygen content is a minor variable in the response to ischemia-reperfusion injury, dwarfed by that from the systemic inflammatory response to CPB.…”
Section: Intraoperative Oxygen and Cognition After Surgerycontrasting
confidence: 89%
“…Bastopcu and Ozhan 1 for their interest and valuable commentary on our article. 2 As they have mentioned, direct sampling of coronary sinus blood was one of the main advantages of our study. 1,2 Needless to say, there were many disadvantages too.…”
mentioning
confidence: 91%
“…2 As they have mentioned, direct sampling of coronary sinus blood was one of the main advantages of our study. 1,2 Needless to say, there were many disadvantages too. Cardiac index measurement was not performed after cardiopulmonary bypass (CPB), because routine use of pulmonary artery catheters, and other forms of thermodilution techniques, in patients undergoing isolated coronary artery bypass grafting (CABG) was already abandoned in our institution at the time of writing of the article.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…We have read with great interest the article "Normoxic management of cardiopulmonary bypass reduces myocardial oxidative stress in adult patients undergoing coronary artery bypass graft surgery" by Topcu et al 1 The authors applied a novel method to determine myocardial oxidative stress and demonstrated increased oxidants in myocardial circulation with hyperoxic management during cardiopulmonary bypass (CPB). We hope that this and other related evidence will guide the cardiac surgeons to further investigate the benefits of perioperative normoxic strategies.…”
mentioning
confidence: 99%